Penerapan Model Pembelajaran Project Based Learning Menggunakan Media Video Tutorial Berbasis Canva untuk Meningkatkan Hasil Belajar Siswa Kelas X di SMK IT Pelita Subana Darma - Purwansyah, Reza; Setiawan, Dena Latif (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine student learning outcomes using the Project Based Learning learning model using Canva-based video tutorial media at SMK IT Pelita Subana Darma. The method used is quantitative with the type of experimental method with the One Group Pre-Test Post-Test Design research design. The population in this study were all class X students of SMK IT Pelita Subana Darma with the sample used in this study, namely class X DKV with a total of 27 students. Research instruments used questions and questionnaires. Data analysis techniques used are validity test, reliability test, data tabulation test, normality test, homogeneity test, hypothesis testing. The results of this study indicate that (1) The results of the application of the project-based learning model using video tutorial learning media show the results of the pretest average questionnaire of 48.52 and the posttest average of 70.00 so that there is an increase of 21.48. (2) Student learning outcomes in drawing subjects before the application of the project-based learning model using canva-based video tutorial learning media (pretest) 54.81 and posttest 78.15. Based on the results of the hypothesis test, the significance value is 0.00, where the significance value is smaller than 0.05 (0.00 <0.05) so it can be concluded that there is a significant effect.